The Role of Vitamin D in Bone Healing and Bone Integration - Henrique Zambon Massaferro; Vinícius Franzão Ganzaroli; Rodrigo Isaías Lopes Pereira; Arthur Nascimento Rocha; Arthur Michellim Kirasuke; Daniela Ponzoni; Marcos Tadeu Adas Saliba (ARCHIVES OF HEALTH INVESTIGATION, 2026)
The historical quest for replacing lost teeth dates back to ancient civilizations, evolving into modern advancements in the field of implant dentistry. This article provides a literature review, highlighting the role of vitamin D in osseointegration and in the practice of implant dentistry. Firstly, a search was conducted in Capes/Cnpq databases, Virtual Health Library, PubMed, and Google Scholar-indexed databases using the following health descriptors (DeCS): Vitamin D, Osseointegration, and Dental Implants. Vitamin D emerges as a critical component in maintaining bone tissue homeostasis, influencing the absorption of calcium and phosphorus, essential for bone remodeling. Despite the clear importance of vitamin D in osseointegration, the shortage of longitudinal studies in humans is evident, emphasizing the need for further research in this area to fully elucidate its influence and optimize clinical outcomes in implant dentistry. This study underscores the need for an integrated approach in implant dentistry practice, considering not only the technical aspects of procedures but also systemic factors such as adequate vitamin D supplementation to promote osseointegration and ensure long- term success of prosthetic rehabilitations on implants.